The Impact of Communication on Employee Performance in F&B Service Department at PRA Hotel, Legian - Pradnya Wiweka, I Gede Giyan; Santi Diwyarthi, Ni Desak Made; H. Sihombing, Irene Hanna (Westscience Press, 2025)
This study aims to examine the influence of communication on employee performance within the Food and Beverage Service department at PRA Hotel, Legian. The research involved a sample of 55 employees, ranging from captain level to supervisory roles and above, who regularly participated in afternoon briefing sessions. The study utilized both quantitative data from the Associate Opinion Survey and qualitative insights gathered through unstructured interviews with the Food and Beverage Manager, as well as several captains and supervisors. Primary data were obtained through questionnaires distributed to selected respondents using purposive sampling. The data analysis employed a simple linear regression model using SPSS version 30 for Windows. The findings indicate that the communication variable (X) has a positive and statistically significant impact on employee performance (Y) in the Food and Beverage Service department at PRA Hotel, Legian.